Investigation of UWB antenna slot effect / Shazliezawaty Saha Hu Hamid - Saha Hu Hamid, Shazliezawaty (2015)
This paper proposes about compact planar ultra wideband antenna having frequency band notch function as presented. The main purpose of using this compact planar ultra wideband antenna is to do the band rejected filtering properties in the WiMAX AVLAN at 2.4 GHZ to 5 GHZ. By etching the slot on the top of the patch and the result are achieve. The parameter that will be considered while doing this project are the matched impedance, stable radiation pattern, band rejection and constant gain. This antenna will be design to operate at certain frequency on FR4 substrate with er = 4.7 and the simulation will be conducted by using Computer Simulation Technology (CST) software. The performance of simulation results of these antennas will be compared and analyzed. The final antenna designs will be fabricated and measured. To conclude the proposed concept, the simulation and measurement results will compared and analyzed. Keyword: Slot, band notched, ultra wideband (UWB) antenna.